Functional vitamin K status and risk of incident chronic kidney disease and microalbuminuria: a prospective general population-based cohort study. Issue 12 (13th December 2020) - Groothof, Dion; Post, Adrian; Sotomayor, Camilo G; Keyzer, Charlotte A; Flores-Guerero, Jose L; Hak, Eelko; Bos, Jens H J; Schurgers, Leon J; Navis, Gerjan J; Gans, Reinold O B; Eelderink, Coby; de Borst, Martin H; et al.
Abstract: Background: Circulating desphospho-uncarboxylated matrix γ-carboxyglutamate (Gla) protein (dp-ucMGP), a marker of vitamin K status, is associated with renal function and may serve as a potentially modifiable risk factor for incident chronic kidney disease (CKD). We aimed to assess the association between circulating dp-ucMGP and incident CKD. Methods: We included 3969 participants with a mean age of 52.3 ± 11.6 years, of whom 48.0% were male, enrolled in the general population–based Prevention of REnal and Vascular ENd-stage Disease study. Study outcomes were incident CKD, defined as either development of an estimated glomerular filtration rate (eGFR) <60 mL/min/1.73 m 2 or microalbuminuria. Associations of dp-ucMGP with these outcomes were quantified using Cox proportional hazards models and were adjusted for potential confounders. Results: Median plasma dp-ucMGP was 363 [interquartile range (IQR) 219–532] pmol/L and mean serum creatinine- and serum cystatin C-based eGFR (eGFRSCr-SCys ) was 95.4 ± 21.8 mL/min/1.73 m 2 . During 7.1 years of follow-up, 205 (5.4%) participants developed incident CKD and 303 (8.4%) developed microalbuminuria. For every doubling of plasma dp-ucMGP, hazard ratios for the development of incident CKD and microalbuminuria were 1.85 [95% confidence interval (CI) 1.59–2.16; P < 0.001] and 1.19 (95% CI 1.07–1.32; P = 0.001), respectively. These associations lost significance after adjustment for baseline eGFRSCr-SCys [0.99 (95% CI 0.88–1.12; P = 0.86)] and baseline age [1.03 (95% CI 0.94–1.14; P = 0.50)], respectively. Conclusions: The associations of plasma dp-ucMGP with incident CKD and microalbuminuria were driven by the respective baseline effects of renal function and age.